Plastomes of Garcinia mangostana L. and Comparative Analysis with Other Garcinia Species - Ching-Ching Wee; Nor Azlan Nor Muhammad; Vijay Kumar Subbiah; Masanori Arita; Yasukazu Nakamura; Hoe-Han Goh (Molecular Diversity Preservation International (MDPI), 2023)
The two varieties of mangosteen (Garcinia mangostana L.) cultivated in Malaysia are known as Manggis and Mesta. The latter is preferred for its flavor, texture, and seedlessness. Here, we report a complete plastome (156,580 bp) of the Mesta variety that was obtained through a hybrid assembly approach using PacBio and Illumina sequencing reads. It encompasses a large single-copy (LSC) region (85,383 bp) and a small single-copy (SSC) region (17,137 bp) that are separated by 27,230 bp of inverted repeat (IR) regions at both ends. The plastome comprises 128 genes, namely, 83 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The plastome of the Manggis variety (156,582 bp) obtained from reference-guided assembly of Illumina reads was found to be nearly identical to Mesta except for two indels and the presence of a single-nucleotide polymorphism (SNP). Comparative analyses with other publicly available Garcinia plastomes, including G. anomala, G. gummi-gutta, G. mangostana var. Thailand, G. oblongifolia, G. paucinervis, and G. pedunculata, found that the gene content, gene order, and gene orientation were highly conserved among the Garcinia species. Phylogenomic analysis divided the six Garcinia plastomes into three groups, with the Mesta and Manggis varieties clustered closer to G. anomala, G. gummi-gutta, and G. oblongifolia, while the Thailand variety clustered with G. pedunculata in another group. These findings serve as future references for the identification of species or varieties and facilitate phylogenomic analysis of lineages from the Garcinia genus to better understand their evolutionary history.